2017
DOI: 10.21037/tlcr.2017.05.08
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical technologies for understanding circulating tumor cell biology and metastasis

Abstract: An understanding of cancer evolution in lung cancer with its associated resistance to therapy can only be achieved with repeated sampling and analysis of the cancer. Given the high risks and costs associated with repeat physical biopsy, alternative technologies must be applied. Several modalities exist for analysis and re-analysis of cancer biology. Among them are the CellSearch platform, the CTC chip, and the highdefinition CTC platform. While the former is primarily able to provide prognosticating informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…For instance, while the CellSearch technology has been useful, it relies on high levels of EpCAM expression on the CTCs. Therefore, methods still need to be developed to detect tumor cells with downregulated epithelial proteins [60].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while the CellSearch technology has been useful, it relies on high levels of EpCAM expression on the CTCs. Therefore, methods still need to be developed to detect tumor cells with downregulated epithelial proteins [60].…”
Section: Discussionmentioning
confidence: 99%
“…CELLSEARCH ® is an FDA approved test for capturing and enumerating CTCs. This method uses ferrofluid reagent, which consists of particles with a magnetic core surrounded by a polymeric layer coated with antibodies targeting the Epithelial cell adhesion molecule (EpCAM) antigen, for capturing CTCs [64]. The CTC chip, a microfluidic device is one of the techniques used for isolation of CTCs.…”
Section: Methodsmentioning
confidence: 99%
“…69 " CTC-chip " test that developed by Chikaishi et al demonstrated better performance than CELLSEARCH®test that is approved by the United States Food and Drug Administration (US FDA). 70,71 Chest pain is common and usually heavy and dull and sometime called a " dragging " sensation, 5,72 Breathlessness is also common and is usually due to a pleural effusion that is identified in about 70 % of MPM patients in early stage of disease. 73 Other clinical features include anorexia, weight loss, malaise, sweats, and fatigue.…”
Section: Clinical Manifestations Investigation and Diagnosismentioning
confidence: 99%